1998
DOI: 10.1063/1.367042
|View full text |Cite
|
Sign up to set email alerts
|

Optical study of silicon-containing amorphous hydrogenated carbon

Abstract: Silicon-containing amorphous hydrogenated carbon films deposited by a plasma-enhanced chemical vapor deposition process were studied using both Raman and ellipsometry spectroscopies. Analyses of the experimental data from both these techniques yielded valuable information about the microstructure of the films. The silicon incorporation in amorphous hydrogenated carbon breaks down large size sp2 carbon clusters and enhances sp3 bonding. The reduction of large sp2 graphitic defects, the enhancement of sp3 bondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 18 publications
3
36
1
Order By: Relevance
“…The bands at 1356 cm − 1 and 1585 cm − 1 are typical D and G peaks of amorphous carbon materials, which suggests that the diamond-like characteristics of the film are retained after being doped with Si. The weak shoulder band at 1150-1200 cm − 1 is assigned to the vibration of transpolyacetylene segments at grain boundaries and surfaces [20], and the broad asymmetric band in the 700~900 cm − 1 region with a maximum around 880 cm − 1 is attributed to the Si-C vibration mode [21,22]. Fig.…”
Section: Characterization Of the A-c:h:si Filmmentioning
confidence: 97%
“…The bands at 1356 cm − 1 and 1585 cm − 1 are typical D and G peaks of amorphous carbon materials, which suggests that the diamond-like characteristics of the film are retained after being doped with Si. The weak shoulder band at 1150-1200 cm − 1 is assigned to the vibration of transpolyacetylene segments at grain boundaries and surfaces [20], and the broad asymmetric band in the 700~900 cm − 1 region with a maximum around 880 cm − 1 is attributed to the Si-C vibration mode [21,22]. Fig.…”
Section: Characterization Of the A-c:h:si Filmmentioning
confidence: 97%
“…The formulas [32] for a smooth absorption edge of amorphous semiconductors were applied for dispersion of ta-C [29], sulphur incorporated nanocrystalline carbon [5]. On the other hand, Lorentzian-like terms or their modifications were used for fluorinated nanocarbon films [11] and other DLC layers [13]. The Lorentzian line approximation…”
Section: Resultsmentioning
confidence: 99%
“…Recently, DLC thin films grown on Si substrates by plasma-enhanced chemical vapour deposition were widely studied [8][9][10][11][12][13][14]. The optical techniques of spectroscopic ellipsometry and Raman light scattering were frequently used for real-time in situ [12,15] and ex situ characterization of DLC films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the positions of both the D and G peaks of a-C:H shift to lower wave numbers as Si is incorporated into the film. 18 It was suggested that the decrease of the Raman frequency upon Si addition occurs because the Si-C bond is weaker than the C-C bond and Si atoms are more massive than C atoms. Carbon atoms in the sp 2 -bonded clusters may be replaced by silicon atoms, reducing the vibrational frequency of the graphitic ring.…”
mentioning
confidence: 99%